2017
DOI: 10.1002/rnc.3996
|View full text |Cite
|
Sign up to set email alerts
|

Actuator and sensor fault detection and isolation for nonlinear systems subject to uncertainty

Abstract: Summary This work addresses the problem of simultaneous actuator and sensor fault detection and isolation (FDI) for control affine nonlinear uncertain systems in the absence of measurement noise. The FDI is achieved by using a bank of filters, which utilize a subset of the measurements along with prescribed values of the control actuators to estimate states and compute expected process behavior. Residuals are next defined as the difference between the observed and expected behavior. Detectability conditions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 34 publications
(60 reference statements)
0
24
0
Order By: Relevance
“…The expected trajectories are calculated using the following prediction model xfalse˜i()k+10.5em=Axfalse˜i()k+italicBu()k1emt[),tkTtk where xfalse˜i is the state of the prediction model, and T is the prediction horizon: T = 1 if 0 < t k ≤ t k ′ , T = k − k ′ if tk<tktk+Tp, and T = T p if tk>tk+Tp, with a positive integer T p being a chosen prediction horizon and t k ′ is the time where for t k ≥ t k ′ the false‖xi()kxfalse^i()kfalse‖d with d being the desired bound on estimation error ( t k ′ thus simply denotes the time at which the observer has converged; see Refs. and for more on this). The prediction model is initialized at the state estimate at time t k ‐ T : xfalse˜i()kT=xfalse^i()kT.…”
Section: Data‐driven Distributed Fdimentioning
confidence: 99%
“…The expected trajectories are calculated using the following prediction model xfalse˜i()k+10.5em=Axfalse˜i()k+italicBu()k1emt[),tkTtk where xfalse˜i is the state of the prediction model, and T is the prediction horizon: T = 1 if 0 < t k ≤ t k ′ , T = k − k ′ if tk<tktk+Tp, and T = T p if tk>tk+Tp, with a positive integer T p being a chosen prediction horizon and t k ′ is the time where for t k ≥ t k ′ the false‖xi()kxfalse^i()kfalse‖d with d being the desired bound on estimation error ( t k ′ thus simply denotes the time at which the observer has converged; see Refs. and for more on this). The prediction model is initialized at the state estimate at time t k ‐ T : xfalse˜i()kT=xfalse^i()kT.…”
Section: Data‐driven Distributed Fdimentioning
confidence: 99%
“…Thus, it is of great importance to design the most adequate controller, and it guarantees the performance of the NCSs subject to different kinds of actuator faults. Further, the robust reliable control analysis has been investigated effectively for continuous‐time systems with mixed actuator failures . By using the equivalent‐input disturbance‐based adaptive reliable control method, Sakthivel et al reported the problem of output tracking control for NCSs with actuator faults and its asymptotic stability.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the robust reliable control analysis has been investigated effectively for continuous-time systems with mixed actuator failures. [15][16][17] By using the equivalent-input disturbance-based adaptive reliable control method, Sakthivel et al 18 reported the problem of output tracking control for NCSs with actuator faults and its asymptotic stability.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, residuals are used to distinguish between system and observer outputs, but these methods are inaccurate and unsuitable for quantifying the magnitude of a fault. By using a bank of filters, with thresholds defined in a way that they explicitly account for the effect of uncertainty, a fault detection and isolation (FDI) approach was proposed to the actuator and sensor fault-diagnosis for nonlinear uncertain systems [34]; another simple and useful approach based on threshold was proposed in [35] by monitoring the error between the load current and current set point, but it is also difficult to find the effective thresholds.…”
Section: Introductionmentioning
confidence: 99%